Pengaruh Kesadaran Merek dan Citra Merek Terhadap Keputusan Pembelian dengan Kepercayaan Merek Sebagai Variabel Mediasi pada Kopi Nako - Bita Utami; Ari Anggarani Winadi Prasetyoning Tyas (Jurnal Manajemen Riset Inovasi, 2024)
This aim examines the effects of brand trust, both direct and indirect, brand image, and brand awareness on purchasing decisions for Kopi Nako. It is driven by the rise in purchasing decisions due to increased brand awareness, which builds brand image and trust. The focus is on individuals who have bought or sampled Kopi Nako at the Monas branch. Data was collected from 110 respondents using purposive sampling and analyzed through SEM. The results show that both brand image and brand awareness have a noteworthy and favorable impact on brand trust. Furthermore, brand awareness and brand image positively influence purchasing decisions, while brand trust has a negative effect on them. Both brand awareness and brand image negatively affect decisions about purchases indirectly by means of brand confidence. The study suggests enhancing brand awareness with effective marketing, maintaining brand popularity through product innovations and positive consumer experiences, and improving brand image by focusing on product quality. Additionally, strengthening brand trust by improving product taste to meet consumer expectations is crucial. These strategies are anticipated to help Kopi Nako improve and maintain consumer purchasing decisions.